LGG-47. SYSTEMIC THERAPY OF ROSETTE-FORMING GLIONEURONAL TUMOR OF THE FOURTH VENTRICLE INAN ADOLESCENT. (4th December 2020) - McNall-Knapp, Rene; Gross, Naina; Zaky, Wafik; Cornwell, Benjamin; Gavula, Theresa; Bavle, Abhishek
Abstract: An 11 y.o. female presented to a GI specialist with complaints of morning vomiting and periumbilical abdominal pain for several months. Had progressing symptoms with GI work-up for ~1 year. She developed diplopia and worsening headaches. Imaging revealed a T2/FLAIR hyperintense mass in the 4 th ventricle with heterogeneous enhancement and obstructive hydrocephalus. Three T2 bright, non-enhancing, subcentimeter masses identified in the right cerebellum. Due to poor differentiation between tumor and normal tissue at brainstem, only partial resection (PR) was feasible. Pathology initially called pilocytic astrocytoma (PA). All symptoms resolved after PR. Slow progression in the tumor and "satellite" lesions noted over two years. Second opinion and molecular typing reclassified the tumor as rosette-forming glioneuronal tumor (RFGNT) with a mutation in PIK3CA. Therapy started with vinblastine and carboplatin with stable disease x 7 months, discontinued due to allergic reaction to carboplatin. Initiated therapy with everolimus, an mTOR inhibitor. The tumor's characteristics on imaging changed with initial growth and increase in peripheral enhancement in one satellite and the primary tumor. Nevertheless, we persevered. When comparing pre-treatment MRI to most recent 7 months later, there has been an overall decrease in volume of expansile heterogenous tumor along the margins of the fourth ventricle. The degree of peripheral enhancement associated with the mass has increased. RFGNT is a rare tumor included in WHO classification since 2007. Ellezam et al identified recurrent PIK3CA mutations. To our knowledge, this is the only report of treatment targeting the mutation. We report a radiographic response despite initial growth.